Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5435/jaaosglobal-d-20-00001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Corticosteroid Use as a Risk Factor for Perioperative Complications in Patients Undergoing Total Joint Arthroplasty

Abstract: Background: Osteoarthritis may be caused by or concurrent with diseases such as rheumatoid arthritis or systemic lupus erythematosus, which rely on chronic corticosteroids regimens for treatment. If a total knee or hip arthroplasty is needed, this chronic treatment method has been associated with poorer surgical outcomes. Methods: A retrospective analysis of data collected by the American College of Surgeons National Surgical Quality Improvement Program was conducted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Recent larger studies [11][12][13][14] confirm data underlying previous recommendations [15,16] indicating a dose-dependent increased risk of perioperative complications, especially infections, with GCs. A retrospective study based on health insurance data from 10,923 RA patients undergoing elective knee or hip replacement showed that the risk of infections leading to hospitalization within 30 days postoperatively was significantly higher in patients receiving 5-10 mg prednisone equivalent/day (OR 1.32) and >10 mg/day (odds ratio [OR] 2.10) compared to patients not receiving GC therapy.…”
Section: Glucocorticoidssupporting
confidence: 63%
See 1 more Smart Citation
“…Recent larger studies [11][12][13][14] confirm data underlying previous recommendations [15,16] indicating a dose-dependent increased risk of perioperative complications, especially infections, with GCs. A retrospective study based on health insurance data from 10,923 RA patients undergoing elective knee or hip replacement showed that the risk of infections leading to hospitalization within 30 days postoperatively was significantly higher in patients receiving 5-10 mg prednisone equivalent/day (OR 1.32) and >10 mg/day (odds ratio [OR] 2.10) compared to patients not receiving GC therapy.…”
Section: Glucocorticoidssupporting
confidence: 63%
“…In a Danish registry-based cohort study, GC was also identified (in addition to increased disease activity) as a risk factor for mortality after knee/hip replacement (HR 2.87) [13]. In another Apremilast can be continued 5 9/10 9.7 The level of agreement (0 = no agreement, 10 = full agreement) is given as a mean value DMARD disease-modifying antirheumatic drugs, GC glucocorticoid, IL interleukin, JAK Janus kinase, LoE level of evidence according to the Oxford Centre for Evidence-Based Medicine [67], MTX methotrexate, TNF tumor necrosis factor retrospective analysis of 14,774 patients undergoing long-term GC therapy for various chronic conditions, significantly more perioperative complications, including wound infections, deep surgical infections, wound dehiscence, pneumonia, urinary tract infections, and re-hospitalization, were found in patients receiving GC compared with patients without GC according to a univariate analysis [14].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Intra-articular corticosteroids do not dissolve quickly [26], and they may persist and lead to local immunosuppression after TJA. Patients with chronic corticosteroid use have a higher likelihood of surgical infection than corticosteroid-naïve patients; this increased likelihood may be caused by corticosteroid suppression of the proliferation of fibroblasts and an inhibition of the ability to remodel collagen [28]. Future studies will likely need to come from registries, national databases, or insurance company data.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary for doctors and nurses to strengthen preoperative assessment. Before surgery, it is necessary to understand the patient’s past medical history, general condition and blood coagulation, strengthen the screening of high-risk patients with DVT, and actively correct the effects of anemia, hypertension, diabetes and other cardiovascular diseases[ 40 ]. During the operation, the doctor should be familiar with the anatomy and surgical techniques, and reduce the operation and anesthesia duration.…”
Section: Discussionmentioning
confidence: 99%